ASSESSMENT OF THE PSYCHOSOCIAL LEARNING ENVIRONMENT FOR BIOLOGY LEARNING IN AKOKO SOUTH WEST IN ONDO STATE, NIGERIA - Grace Titilope Babafemi (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
The role of psychosocial factors in improving students learning is well documented in literature, as well as its prospects and benefits in addressing educational problems. Hence the need to assess the psychosocial learning environment for biology learning. This study revealed biology students’ anxiety level, their sense of belonging and the classroom climate as perceived by the students. The descriptive survey research was conducted with 391 biology students selected randomly from a population of all senior secondary school biology students in Akoko South West, Ondo State, Nigeria. A four-sectioned validated questionnaire, with reliability index of 0.72, 0.82, and 0.77, served data collection purpose. Findings revealed that students’ anxiety level is moderate (mean score=1.49). Although, students often get depressed if they don’t perform up to expectation (1.27), they are not anxious whenever test is approaching (1.54), and they are unsure of their anxiety level with respect to failing (1.50). Also, students exhibit a moderately high sense of belongingness in school (mean=1.68) but students feel ignored in most extra-curricular activities (1.31) and believe that their teachers are often too busy to attend to their personal needs (1.28). Students accepts their classroom climate as conducive for learning (1.76), organized (1.74), and not disoriented (1.59). The result also reveals that the classroom atmosphere is moderately positive (mean=1.66). It was recommended that educational stakeholder and curriculum implementers should employ techniques that will further decrease students’ anxiety and boost their sense of belonging. The classroom climate should be supplemented with psychosocial enrichment. Keywords: Psychosocial Learning Environment, Anxiety, Sense of Belonging, Biology